Changes in medical management and colectomy rates: a population‐based cohort study on the epidemiology and natural history of ulcerative colitis in Örebro, Sweden, 1963‐2010. Issue 8 (17th August 2017) - Eriksson, C.; Cao, Y.; Rundquist, S.; Zhulina, Y.; Henriksson, I.; Montgomery, S.; Halfvarson, J.
Summary: Background: Whether the epidemiology of ulcerative colitis (UC) has changed during recent decades is partly unknown. Aim: To depict temporal trends in the epidemiology and medical treatment of UC as well as the long‐term risk of progression in disease extent and colectomy, during 1963‐2010. Methods: Patients were identified by evaluation of all medical records in the archive of the Colitis Clinic, Örebro University Hospital. Comparisons were made between three time periods, 1963‐1975, 1976‐1990 and 1991‐2005. Results: The annual age‐standardised incidence increased from 3.5 to 18.5 per 100 000 during the study period ( P < .01). Correspondingly, the prevalence increased from 44 to 474 per 100 000 between 1965 and 2010. A higher proportion of males than females had extensive colitis at diagnosis (odds ratio: 1.55; 95% CI 1.17‐2.05; P < .01). The risk for progression in disease extent was 34.5% and 18.5% at 10 years, for patients with proctitis and left‐sided colitis, respectively ( P < .01). The use of 5‐aminosalicylates, within 10 years, rise from 79% to 92% between 1963‐1975 and 1976‐1990 ( P < .01). Thiopurine use increased from 7% in 1976‐1990 to 34% during 1991‐2005 ( P < .01). The colectomy rate at 10 years was 13.5% (95% CI 11.1%‐15.8%), and the risk was lower among patients diagnosed in 1991‐2005 compared to 1963‐1975 (adjusted hazard ratio: 0.61; 95% CI 0.39‐0.94; P = .02). Conclusion: The incidence and prevalence of UC increased over time, and the observed prevalence in 2010 is among the highest reported. In parallel, a decrease in colectomy rates was observed during the most recent decades, potentially reflecting improved medical treatment. Abstract : Linked Content This article is linked to Alin et al and Eriksson and Cao papers. To view these articles visithttps://doi.org/10.1111/apt.14292 andhttps://doi.org/10.1111/apt.14336 .